Oral candidiasis (oral thrush) - Khaled darz, Nezar (faculty of Basic Medical Science - Libyan International Medical University, 2020)
Background: Oral Candidiasis is one of the recurrent fungal infection affecting the oral mucosa. It is a commensal organism of normal oral flora which is capable of opportunistic infections. Candida albicans are recovered from 60% of dentate patients mouth over the age of 60 years. There are three general factors which allows the Candida albicans contamination to develop inside the patient’s body includes Immune status of the patient, oral mucosal environment, and strain of Candida albicans . Early sign of host protection breakdown is neutropenia whereas risk factors include: antibiotics, immunosuppression, diabetes, HIV, steroids, nutritional deficiency, Radiation/Chemotherapy
Oral candidiasis is recurrent infections of the oral cavity caused by an uncontrold growth of Candida species, fungi are free-living, eukaryotic organisms that exist as yeasts (round fungi), moulds (filamentous fungi), or both (dimorphic fungi). Candida normally lives on the skin and inside the body, in places like the mouth, throat, gut, and vagina, without causing any problems. Oral candidiasis is a significant source of morbidity, as it can cause chronic pain or discomfort upon mastication, limiting nutrition intake in the elderly or immunodeficient patients. Regional or systemic factors may be predisposing factors for oral candidiasis. For example, the local causes, salivary gland dysfunction, and saliva constituents such as histidine-rich polypeptides, lactoferrin, and lysozyme may be predisposed to oral candidiasis. (Scully et al., 1994; Ship & Turner, 2007). Dental prostheses create a favorable micro-environment for the growth of candida species. Around 65 per cent of full denture wearers are predisposed to candida infection. (Martori et al., 2005; Ashman and Farah, 2014). The use of topical or inhalational corticosteroids and overzealous use of antimicrobial mouthwashes may be another significant local factor that raises the risk of oral candidosis. We temporarily remove local immunity and induce changes in the oral flora (Scully et al., 1994; Jainkittivong et al., 2007). Some research indicate that smoking alone or in conjunction with other factors significantly affects the carriage of oral candida while the possible reasons for promoting colonization of candida include localized epithelial changes caused by smoking (Arendorf and Walker, 1980). Unbalanced dietary intake of refined sugars, carbohydrates, and dairy products (with a high lactose content) may be likely serve as Development enhances by reducing pH levels and thereby encouraging the production of candida species (Martins et al., 2014).